2019
DOI: 10.1007/s11469-019-00069-2
|View full text |Cite
|
Sign up to set email alerts
|

A Tool to Help or Harm? Online Social Media Use and Adult Mental Health in Indonesia

Abstract: The effect of online social media use on individual mental health remains contested. This study examines the effect of online social media (Facebook, Twitter, and chat) on adult mental health in Indonesia. Instrumental variable analysis was used to address reverse causality issues. Data come from the Indonesia Family Life Survey (IFLS) 2014, which polled 22,423 individuals age 20 years and older in 9,987 households and 297 districts in Indonesia. The findings show that social media use harms adult mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 83 publications
(118 reference statements)
0
25
0
Order By: Relevance
“…CES-D score was calculated as the sum of responses to the 10 items after the positively phrased items were reverse-coded. Scores range from 0 to 30, with high scores indicating higher levels of depressive symptoms (Sujarwoto et al, 2019). A cutoff point of 10 is used to identify depression in an individual (Fahmi et al, 2019;Tran et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…CES-D score was calculated as the sum of responses to the 10 items after the positively phrased items were reverse-coded. Scores range from 0 to 30, with high scores indicating higher levels of depressive symptoms (Sujarwoto et al, 2019). A cutoff point of 10 is used to identify depression in an individual (Fahmi et al, 2019;Tran et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Research shows that there is a relationship between the time spent using social media and feelings of depression and anxiety in adolescents (Banjanin et al, 2015;Barry et al, 2017;Pantic et al, 2012;Woods & Scott, 2016). Further, Sujarwoto et al (2019) found an influence between the use of social media and mental health in developing countries, such as in Indonesia. Hormes et al (2014) found that high social media use causes difficulties in emotion regulation.…”
Section: Conceptual Model and Research Hypothesismentioning
confidence: 99%
“…Emotion regulation is awareness, clarity, acceptance, access, ability to control, and ability to response through emotional responses (Gratz et al, 2004). Emotional regulation is considered important because excessive use of social media can cause depression, especially for people in developing countries, such as in Indonesia (Sujarwoto et al, 2019). In addition, Zahniser and Conley (2018) have shown that difficulties with emotion regulation are associated with indicators of stress or perceived stress in emerging adults.…”
Section: Conceptual Model and Research Hypothesismentioning
confidence: 99%
“…As such, the role of social media during the corona-outbreak can be understood as ambiguous, as on the one hand it enabled people to stay in touch and be updated on the situation, while at the same time contributing to substantial stress and worry. For example, research has shown that social media may create a sense of community and connectedness [12] and increase one's social capital [13], but also that it may increase symptoms of anxiety and depression [10,14].…”
Section: Introductionmentioning
confidence: 99%